Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1371/journal.pone.0125643
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Enablers of Kangaroo Mother Care Practice: A Systematic Review

Abstract: Kangaroo mother care (KMC) is an evidence-based approach to reducing mortality and morbidity in preterm infants. Although KMC is a key intervention package in newborn health initiatives, there is limited systematic information available on the barriers to KMC practice that mothers and other stakeholders face while practicing KMC. This systematic review sought to identify the most frequently reported barriers to KMC practice for mothers, fathers, and health practitioners, as well as the most frequently reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
293
2
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(326 citation statements)
references
References 56 publications
19
293
2
12
Order By: Relevance
“…The systematic review by Seidman et al 25 proposed that resource-related barriers (eg, lack of guidelines/education) and sociocultural barriers (eg, concerns about medical conditions/care) negatively affected nurses; our study supports these points. Furthermore, other studies also proposed that lack of knowledge and skills were main barriers to KC implementation,23 26–29 as well as medical staff reluctance to allow KC 10 28–30.…”
Section: Discussionsupporting
confidence: 81%
“…The systematic review by Seidman et al 25 proposed that resource-related barriers (eg, lack of guidelines/education) and sociocultural barriers (eg, concerns about medical conditions/care) negatively affected nurses; our study supports these points. Furthermore, other studies also proposed that lack of knowledge and skills were main barriers to KC implementation,23 26–29 as well as medical staff reluctance to allow KC 10 28–30.…”
Section: Discussionsupporting
confidence: 81%
“…Other studies in low-resource settings have also reported knowledge of these benefits [56][57][58]. In particular, the effect of KMC on parent-infant bonding has been widely reported [9, [59][60][61][62][63]. In this study, most parents stated that the mother is the KMC provider.…”
Section: Acceptabilitymentioning
confidence: 67%
“…Findings from one of the most recent and comprehensive systematic reviews of the barriers and promoters of SSC (included in the complete package known as Kangaroo Mother Care)23 identified over 35 factors involved in integrating SSC into the NICU environment. The top three barriers to SSC were issues with the NICU physical facility, negative impressions by the staff about the practice and fear of injuring the infant during SSC.…”
Section: Introductionmentioning
confidence: 99%